PENERAPAN STRATEGI RECIPROCAL TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMPN 25 PEKANBARU - Dwi Nurul Putri; Maimunah Maimunah; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was classroom action research that aims to improve learning process and to increase learning result in mathematics with applied the learning strategy of reciprocal teaching. The subject of this research was student of class VII1 SMPN 25 Pekanbaru in academic years 2017/2018, which amounted to 34 students, consist of 9 boys and 25 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to UH-I and UH-II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (47,06%) to the first UH-I (61,76%) to the UH-II (76,47%) thus it can be concluded that the application of reciprocal teaching strategy can improve learning process and increase mathematics achievement from the students at class VII1 SMPN 25 in academic years 2017/2018 for the social arithmetic.Key Words: Students’ Mathematic Achievement, Reciprocal Teaching, Class Action Research